The emerging role of photorespiration and non‐photorespiratory peroxisomal metabolism in pathogen defence. (18th March 2013) - Sørhagen, K.; Laxa, M.; Peterhänsel, C.; Reumann, S.
Abstract: Photorespiration represents one of the major highways of primary plant metabolism and is the most prominent example of metabolic cell organelle integration, since the pathway requires the concerted action of plastidial, peroxisomal, mitochondrial and cytosolic enzymes and organellar transport proteins. Oxygenation of ribulose‐1, 5‐bisphosphate by Rubisco leads to the formation of large amounts of 2‐phosphoglycolate, which are recycled to 3‐phosphoglycerate by the photorespiratory C2 cycle, concomitant with stoichiometric production rates of H2 O2 in peroxisomes. Apart from its significance for agricultural productivity, a secondary function of photorespiration in pathogen defence has emerged only recently. Here, we summarise literature data supporting the crosstalk between photorespiration and pathogen defence and perform a meta‐expression analysis of photorespiratory genes during pathogen attack. Moreover, we screened Arabidopsis proteins newly predicted using machine learning methods to be targeted to peroxisomes, the central H2 O2 ‐producing organelle of photorespiration, for homologues of known pathogen defence proteins and analysed their expression during pathogen infection. The analyses further support the idea that photorespiration and non‐photorespiratory peroxisomal metabolism play multi‐faceted roles in pathogen defence beyond metabolism of reactive oxygen species.